Distribution of inception times in repetitive pulsed discharges in synthetic air. (11th November 2020) - Mirpour, S; Martinez, A; Teunissen, J; Ebert, U; Nijdam, S
Abstract: Knowing which processes and species are responsible for discharge inception is important for being able to speed up, delay, or completely avoid it. We study discharge inception in 500 mbar synthetic air by applying 10 ms long 17 kV pulses with a repetition frequency of 2 Hz to a pin-to-plate electrode geometry with a gap length of 6 cm. We record inception times for hundreds of pulses by measuring the time delay between the rising edge of the high-voltage (HV) pulse and the signal from a photo-multiplier tube. Three characteristic time scales for inception are observed: (1) 20 ns, (2) 25 μ s, and (3) 125 μ s. To investigate the underlying processes, we apply a low-voltage (LV) pulse in between the HV pulses. These LV pulses can speed up or delay discharge inception, and our results suggest that the three time scales correspond to: (1) free electrons or electron detachment from negative ions close to the electrode, (2) a process that liberates electrons from (quasi)-neutrals, and (3) the drift of an elevated density of negative ions to the ionization zone. However, each of these explanations has its caveats, which we discuss. We present a theoretical analysis of the distribution of inception times, and perform particle simulations in the experimental discharge geometry. Some of the observed phenomena can be explained by these approaches, but a surprizing number of open questions remain.